Nonlinear parametric interactions in ion-implanted semiconductor plasmas having strain-dependent dielectric constants. (January 2017) - Yadav, N; Ghosh, S; Malviya, P S
Abstract : We report nonlinear parametric interactions using a hydrodynamic model of ion-implanted semiconductor plasmas having strain-dependent dielectric constants (SDDC). High-dielectric-constant materials are technologically important because of their nonlinear properties. We find that the third-order susceptibility varies in the range 10 − 14 –10 − 12 m 2 · V − 2 for ion-implanted semiconductor plasmas, which is in good agreement with previous results. It is found that the presence of SDDC in ion-implanted semiconductor plasma modifies the characteristic properties of the material.